New approaches to recruitment and selection - Trompenaars, Fons; Woolliams, Peter (The new business culture, 2024)
Current recruitment and selection practices are essentially a cloning process which seeks to match applicants with the current corporate culture of the hiring organisation. This ignores applicants with different points of view, differing value systems and career aspirations. Authors Fons Trompenaars and Peter Woolliams explore the idea that, while all organisations should develop and promote their core values, the application of them needs to be revisited. New Approaches to Recruitment and Selection presents a new framework that compares current corporate cultures with the evolving value systems of current and potential employees. The authors believe that applicants should match the organization's needs and explore how different categories of applicants can enrich the organisation whilst providing full engagement. The authors' longitudinal research on traditional frameworks and practices shows that while companies strive to be objective, they are rarely free of cultural bias. They identify serious shortcomings in how organisations utilise their people. While most organisations are implementing a wide range of policies and programmes to identify and eliminate pay inequalities, and improve their attractiveness to women and minorities, great change has not materialised. Each volume in this series will explore failing established models and propose new conceptual frameworks with practical approaches. International case studies enrich the arguments and findings. Purchase of this book includes exclusive access to app-based content, enabling readers to explore the application of specific concepts in further detail.